Secrets of power presentations : - Holliday, Micki. (Career Press, 2000)
Designed to help you overcome the fear of public speaking. Covers all the new multimedia aids to presentations and reveals the key to controlling your fears. Details how to outline and organize an effective presentation, improve your style of delivery, and capture and maintain the attention of your audience. Softcover. DLC: Business presentations.